Waste less time on Facebook — follow Brilliant.
×

Functional Equation

Find all functions, \(f : \mathbb{R} \rightarrow \mathbb{R},\) such that

\[f(x+y) - 2f(x-y) + f(x) - 2f(y) = y-2.\]

Note by Victor Loh
3 years, 2 months ago

No vote yet
1 vote

  Easy Math Editor

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 \( 2 \times 3 \)
2^{34} \( 2^{34} \)
a_{i-1} \( a_{i-1} \)
\frac{2}{3} \( \frac{2}{3} \)
\sqrt{2} \( \sqrt{2} \)
\sum_{i=1}^3 \( \sum_{i=1}^3 \)
\sin \theta \( \sin \theta \)
\boxed{123} \( \boxed{123} \)

Comments

Sort by:

Top Newest

Let \(P(x,y)\) be the statement \(f(x+y)-2f(x-y)+f(x)-2f(y)=y-2\).

\(P(0,0)\implies f(0)=1\)

\(P(x,x)\implies f(2x)=f(x)+x\)

\(P(x,-x)\implies f(x)+2f(-x)=3-x\stackrel{x\to -x}\implies f(-x)+2f(x)=3+x\)

\(\implies f(x)+f(-x)=2\)

The last one was got by adding the 2 previous equations.

\((2-f(x))+2f(x)=3+x\implies f(x)=x+1\)

Thus \(f(x)=x+1\) is the only possible solution. After checking it we see it works.\(\square\)

Mathh Mathh - 3 years, 2 months ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...